A Simple Experiment of Block Coding Reed Solomon (15,5) using Matlab Simulink - Subagja, Banda; Jannah, Fauziyah Rhaudhatul; Agnesia, Gisella; Suranegara, Galura Muhammad; Setyowati, Endah (Telecommunications, Networks, Electronics, and Computer Technologies (TELNECT), 2021)
In recent years, technical developments in telecommunications have made rapid progress in providing the increase of reliable and efficient communication services. The reliability provided is used to overcome interruptions during communication. Since the problem is caused by corrupted transmitted data, an encoder and coding decoder are needed to correct the problem. Reed-Solomon (RS) coding is commonly used as forwarding Error Correction (FEC) code for correcting errors. Burst errors, noise effects, and corrupted data are all solved with this method. Data transfer is carried out using the parity check process, which involves applying a number of bits to the data blocks that have been broken at the encoder level, then repairing each block and returning the original data to the decoder. The aim of this paper is to explain and analyze the Bit Error Rate (BER) that occurs by using the integer random code block technique in Reed-Solomon coding (15,5) and to simulate the output in the Matlab.